Self-Nanoemulsifying Drug Delivery System (SNEDDS) for Oral Delivery of Cod Liver Oil - Sani Ega Priani; Desti Puspa Rahayu; Indra Topik Maulana (Borneo Journal of Pharmacy, 2021)
Cod liver oil (CLO) has long been used as medicine or as a functional food. The CLO is a potential source of vitamin D, vitamin A, and omega fatty acids (eicosapentaenoic acid/EPA and docosahexaenoic acid/DHA). Self-nanoemulsifying drug delivery system (SNEDDS) can enhance dissolution, absorption, and bioavailability of hydrophilic and lipophilic substances for oral administration. The objective of this study was to develop a SNEDDS of CLO with good physical characteristics and stability. The optimization formula was carried out using various ratios of oil, surfactant, and cosurfactant. The physical properties of SNEDDS were determined by transmittance percentage, dispersibility, robustness, thermodynamics stability (heating-cooling cycle, centrifugation, and freeze-thaw cycle), and globule size distribution. The optimum formula of CLO-SNEDDS was obtained at a ratio of surfactant and cosurfactant 2 : 1 and a comparison of oil and surfactant mixtures 1 : 6. The CLO-SNEDDS meets the requirement of percent transmittance (97.90±0.85), dispersibility (grade A), and stability based on robustness and thermodynamic stability tests. Diluted SNEDDS has an average globule size of 125 nm with a polydispersity index (PDI) of 0.515. CLO-SNEDDS preparation has good physical characteristics and stability.